2013
DOI: 10.1364/josab.30.002882
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz emission from ZnGeP_2: phase-matching, intensity, and length scalability

Abstract: Collinear phase-matched optical rectification is studied in ZnGeP2 pumped with near-infrared light. The pumpintensity dependence is presented for three crystal lengths (0.3, 1.0 and 3.0 mm) to determine the effects of linear optical absorption, nonlinear optical absorption and terahertz free-carrier absorption on the generation. Critical parameters such as the coherence length (for velocity matching), dispersion length (for linear pulse broadening) and nonlinear length (for self-phase modulation) are determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Chalcogenides and pnictides based ternary tetrahedral (A II B IV C 2 V and A I B III C 2 VI ) semiconductors, which build a broader class of semiconducting materials with varied structural, mechanical, electrical, and optical properties and have attracted interest because of their growing scientific and technological applications. Among complex solids, ternary compounds are semiconductors having a large energy direct band gap, strong non linearity, low thermal conductivity, broad transparency window, lower melting temperatures, and a tetragonal chalcopyrite crystal structure [1][2][3][4][5][6]. Once studied for their low thermal conductivities, currently they are investigated for applications like as electromagnetic (EM) screening, spintronics [7][8], and photovoltaics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenides and pnictides based ternary tetrahedral (A II B IV C 2 V and A I B III C 2 VI ) semiconductors, which build a broader class of semiconducting materials with varied structural, mechanical, electrical, and optical properties and have attracted interest because of their growing scientific and technological applications. Among complex solids, ternary compounds are semiconductors having a large energy direct band gap, strong non linearity, low thermal conductivity, broad transparency window, lower melting temperatures, and a tetragonal chalcopyrite crystal structure [1][2][3][4][5][6]. Once studied for their low thermal conductivities, currently they are investigated for applications like as electromagnetic (EM) screening, spintronics [7][8], and photovoltaics [9].…”
Section: Introductionmentioning
confidence: 99%
“…The THz was created from (012)-cut zinc germanium di-phosphide pumped with 1540 nm light and detected in the time-domain using electrooptic sampling; the spectra were obtained using a numerical Fourier transform. 21,22 UV-Visible absorption spectra were taken in diffuse reflection using an integrating sphere and a Shimadzu 2550 UV-VIS spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Determining these optical parameters is the prerequisite for optical sensitive detection and is an important design index for developing new optical sensors. Studies on the optical coefficients of biological samples have shown that the optical properties of such samples generally cannot be measured directly and must be derived via experimental measurement combined with corresponding theories, commonly used prism coupling, spectral measurement, and elliptic polarization methods [15][16][17][18]. Among them, the elliptic polarization method is the most suitable for measuring parameters, such as the thickness, surface roughness, and optical constant of thin-film or block materials.…”
Section: Introductionmentioning
confidence: 99%